The Effect of Microsoft Whiteboard-Assisted Environmental Mathematics towards Environmental Care Attitudes of Pre-Service Elementary School Teachers - Prihastari, Ema Butsi; Widyaningrum, Ratna (FKIP Universitas Lampung, 2022)
The low concern for the environment after the pandemic period which gradually ended, especially when learning in Higher Education has been carried out face-to-face. There are indications of an increasing amount of litter and an acute sense of indifference. This study determines the influence and effectiveness of the application of Microsoft whiteboard-assisted environmental mathematics on students' environmental care attitudes. The research population is pre-service elementary school teachers in semester 4 who took part in geometry and measurement courses in elementary schools and the research sample was 69 pre-service elementary school teachers in semester 4 in the course with a simple random sampling technique. Data collection techniques use environmental care questionnaires, observations, and documentation. The data analysis technique uses paired sample t test and N-gain. Based on the results of data analysis, it was found that the value of t count = 10.197 > t table = 2.201, so there is an influence of the influence of the application of Microsoft whiteboard assisted environmental mathematics on students' environmental care attitudes and an N-gain value of 56% is got, so the application of Microsoft whiteboard-assisted environmental mathematics is quite effective in improving student environmental care attitudes. Keywords: math environment, Microsoft whiteboard, care environment. DOI: http://dx.doi.org/10.23960/jpmipa/v23i2.pp486-495